An acid-free anionic oxoborane isoelectronic with carbonyl: facile access and transfer of a terminal B═O double bond - Loh, YK; Porteous, K; Fuentes, MÁ; Do, D; Hicks, J; Aldridge, S (American Chemical Society, 2019)
We disclose the synthesis and structural characterization of the first acid-free anionic oxoborane, [K(2.2.2-crypt)][(HCDippN)2BO] (1) (Dipp = 2,6- iPr2C6H3), which is isoelectronic with classical carbonyl compounds. 1 can readily be accessed from its borinic acid by a simple deprotonation/sequestration sequence. Crystallographic and density functional theory (DFT) analyses support the presence of a polarized terminal B═O double bond. Subsequent π bond metathesis converts the B═O bond to a heavier B═S containing system, affording the first anionic thioxoborane [K(2.2.2-crypt)][(HCDippN)2BS] (2), isoelectronic with thiocarbonyls. Facile B═O bond cleavage can also be achieved to access B-H and B-Cl bonds and, via a remarkable oxide (O2-) ion abstraction, to generate a borenium cation [(HCDippN)2B(NC5H5)][OTf] (4). By extension, 1 can act as an oxide transfer agent to organic substrates, a synthetic role traditionally associated with transition-metal compounds. Hence we show that B-O linkages, which are often considered to be thermodynamic sinks, can be activated under mild conditions toward bond cleavage and transfer, by exploiting the higher reactivity inherent in the B═O double bond.